2020
DOI: 10.1021/acs.jpclett.0c02008
|View full text |Cite
|
Sign up to set email alerts
|

Emission States Variation of Single Graphene Quantum Dots

Abstract: Graphene quantum dots (GQDs) are nanoparticles that consist of a nanometer-sized core of graphene with diverse chemical groups on its boundary. Due to their advantageous properties, they are considered to be a promising material for optoelectronics, bioimaging, or photovoltaics. Despite considerable efforts that have been focused on unraveling the mechanism of their photoluminescence, many fundamental details are still unclear. Here, we report on a single-particle multimodal study that provides new insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…4b, c . The width of the main emission peak distribution was ~43 meV (~15 nm), which was narrower than that of the reported single CD at ~180–480 meV (~40–120 nm) 38 , 39 . Statistical analysis of peak positions and spectral band separation in single-particle spectra revealed that the single CD PL was nearly identical to that of the CDs at the ensemble level, with well-resolved vibrionic structures, and it was consistent with nearly monodisperse optical properties 40 .…”
Section: Resultscontrasting
confidence: 62%
“…4b, c . The width of the main emission peak distribution was ~43 meV (~15 nm), which was narrower than that of the reported single CD at ~180–480 meV (~40–120 nm) 38 , 39 . Statistical analysis of peak positions and spectral band separation in single-particle spectra revealed that the single CD PL was nearly identical to that of the CDs at the ensemble level, with well-resolved vibrionic structures, and it was consistent with nearly monodisperse optical properties 40 .…”
Section: Resultscontrasting
confidence: 62%
“…Nevertheless, a universally accepted explanation is still missing. Using a single-particle based multimodal study, Chizhik and colleagues showed that the PL of individual GQDs primarily depends on the structure of the dot itself rather than the surrounding chemical environments . Interestingly, the adopted synthesis methodology determines the structure of the dot.…”
Section: A Few Examples Showing Well-characterized Cds Are Promising ...mentioning
confidence: 99%
“…Graphene nanoribbons (GNRs) [1,2], graphene quantum dots (GQDs) or graphene nanosheet [3], twisted bilayer graphene (TwBLG) and its heterostructures can not only adjust the energy band structure of zero band gap [4][5][6][7][8], but also present novel physical properties superior to 2D graphene materials [9][10][11][12] (superconductivity, topology, frac-tional quantum Hall effect and so on). These physical properties make the above-mentioned micro-nano materials extremely widely used in the field of optoelectronics [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%